2013
DOI: 10.1017/s1751731112001437
|View full text |Cite
|
Sign up to set email alerts
|

Effect of harvest time and physical form of alfalfa silage on chewing time and particle size distribution in boli, rumen content and faeces

Abstract: The study examined the effects of physical form and harvest time of alfalfa silage on eating and ruminating activity and particle size distribution in feed boli, rumen content and faeces in dry cows. The alfalfa crop was harvested at two stages of growth (early: NDF 37%, late: NDF 44% in dry matter (DM)), and from each harvest, a chopped (theoretical cutting length: 19 mm) and an unchopped crop was ensiled in bales. The silages were fed restrictively to four rumen cannulated non-lactating Jersey cows (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Grinding feedstuffs before in situ rumen incubation is done to improve representative sampling and to attain Dacron bag residues with particle size dimensions that reflect those of particles retained in the rumen in an in vivo situation. Using particle dimensions of washed feces particles for estimation of dimensions in particles escaping the rumen (Jalali et al, 2012a) showed that the screen size of 1.5 mm resulted in biologically realistic particle dimensions of Dacron bag residues after in situ rumen incubation: PL and PW for I00, I24, and I288 fractions from grass and alfalfa silages (Table 4) were about twice as high as PL (1.2 mm) and PW (0.2 mm) of washed feces particles from either sheep fed grass silage (Jalali et al, 2012a), small ruminants fed grass hay or grass seed straw (PL = 1.1 mm; PW = 0.2 mm; Jalali et al, 2012b), or cattle fed alfalfa silage (PL = 1.2 mm; PW = 0.3 mm; Kornfelt et al, 2013).…”
Section: Particle Size Development In Dacron Bag Residues Analyzed Bymentioning
confidence: 94%
“…Grinding feedstuffs before in situ rumen incubation is done to improve representative sampling and to attain Dacron bag residues with particle size dimensions that reflect those of particles retained in the rumen in an in vivo situation. Using particle dimensions of washed feces particles for estimation of dimensions in particles escaping the rumen (Jalali et al, 2012a) showed that the screen size of 1.5 mm resulted in biologically realistic particle dimensions of Dacron bag residues after in situ rumen incubation: PL and PW for I00, I24, and I288 fractions from grass and alfalfa silages (Table 4) were about twice as high as PL (1.2 mm) and PW (0.2 mm) of washed feces particles from either sheep fed grass silage (Jalali et al, 2012a), small ruminants fed grass hay or grass seed straw (PL = 1.1 mm; PW = 0.2 mm; Jalali et al, 2012b), or cattle fed alfalfa silage (PL = 1.2 mm; PW = 0.3 mm; Kornfelt et al, 2013).…”
Section: Particle Size Development In Dacron Bag Residues Analyzed Bymentioning
confidence: 94%
“…To describe the feeding situation and its efficiency under field condition, fecal PS evaluation might be a useful tool [21] [22] [23]. The fecal PS distribution has been measured using dry sieving [16] [15] or wet sieving technics [13] [14].…”
Section: Discussionmentioning
confidence: 99%
“…The ADL content in MT3 (22.82% of DM) was lower than that in CA (24.72% of DM), but higher than in the other treatments. Due to the difficulty in digesting ADL, it stayed in the rumen for a long period [28]. Particles are chewed by cashmere goats repeatedly, such that the number of particles and surface area of the cell walls are increased, in turn increasing the chance that bacteria can reach the fibre and colonise it [29].…”
Section: Discussionmentioning
confidence: 99%